Environmental variables influencing the expression of morphological characteristics in clones of the forage cactus (Revista Ciência Agronômica, 2018)
The environmental factors that affect the morphological characteristics of different genera of cacti are littleknown. The aim of this study therefore was to analyse the contribution of environmental variables to growth in cladodes andplant of forage cactus clones of the genera Nopalea and Opuntia. The data used in this study were obtained from an experimentconducted in Serra Talhada, Pernambuco, Brazil, between 2012 and 2013, where the clones ‘IPA Sertânia’ (Nopalea), ‘Miúda’(Nopalea) and ‘Orelha de Elefante Mexicana’ (Opuntia) were submitted to different irrigation depths (2.5, 5.0 and 7.5 mm) andfixed irrigation intervals (7, 14 and 28 days). Morphological characteristics of the cladodes and plants and weather variableswere obtained over time. Pearson’s correlation, followed by multicollinearity, canonical and path analysis were applied. Theminimum temperature, maximum and minimum relative humidity, wind speed and solar radiation were the variables thatmost affected growth in the cactus. The genus Opuntia showed less sensitivity to variations in air temperature compared tothe genus Nopalea. The higher intensities of global solar radiation affected clones of the genus Nopalea more than the genusOpuntia. It can be concluded that there are different environmental requirements between forage cacti of the genera Nopaleaand Opuntia.